APPLICATION OF PROJECT-BASED LEARNING ASSISTED BY MICROSOFT MATHEMATICS TO IMPROVE STUDENTS' MATHEMATICAL REPRESENTATION ABILITY - Dayana Sabila Husain; Rafika Meiliati; Nuralda Nuralda; Aswin Aswin; Achmad Salido (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study examined the effect of Project-based Learning (PjBL) assisted by Microsoft Mathematics on students’ mathematical representation ability. A quasi-experimental design with a posttest-only control group was employed in two tenth-grade classes at a senior high school in Kolaka Regency. The experimental group received PjBL with Microsoft Mathematics, while the control group was taught conventionally. Data were collected through a representation test, a questionnaire, and an observation sheet, and analyzed using both descriptive and inferential statistics. Results showed that the experimental group achieved a significantly higher mean score (81.17) than the control group (60.19), with a mean difference of 20.99 points (p < 0.05). The questionnaire findings revealed very positive student perceptions, indicating that Microsoft Mathematics was easy to use, helpful in understanding concepts, and improved problem-solving skills, while also fostering interest and independence. Observation confirmed that PjBL was implemented effectively: teachers provided clear guidance, students designed projects, collaborated, and presented outcomes through various representations using Microsoft Mathematics. These findings demonstrate that combining PjBL with technology strengthens students’ mathematical representation ability and enriches learning. The study implies that technology-supported project learning can serve as an effective model for promoting meaningful, engaging, and skill-oriented mathematics education in secondary schools.Penelitian ini mengkaji pengaruh Project-based Learning (PjBL) berbantuan Microsoft Mathematics terhadap kemampuan representasi matematis siswa. Desain penelitian yang digunakan adalah kuasi-eksperimen dengan kelompok kontrol posttest-only pada dua kelas X di salah satu SMA di Kabupaten Kolaka. Kelompok eksperimen mendapatkan pembelajaran PjBL dengan Microsoft Mathematics, sedangkan kelompok kontrol diajar secara konvensional. Data dikumpulkan melalui tes representasi, angket, dan lembar observasi, kemudian dianalisis dengan statistik deskriptif dan inferensial. Hasil penelitian menunjukkan bahwa kelompok eksperimen memperoleh skor rata-rata yang secara signifikan lebih tinggi (81,17) dibandingkan kelompok kontrol (60,19), dengan selisih rata-rata 20,99 poin (p < 0,05). Temuan angket menunjukkan persepsi siswa yang sangat positif, bahwa Microsoft Mathematics mudah digunakan, membantu dalam memahami konsep, meningkatkan keterampilan pemecahan masalah, sekaligus menumbuhkan minat dan kemandirian. Hasil observasi menegaskan bahwa PjBL terlaksana secara efektif: guru memberikan arahan yang jelas, siswa merancang proyek, berkolaborasi, serta mempresentasikan hasil melalui berbagai bentuk representasi dengan Microsoft Mathematics. Temuan ini menunjukkan bahwa menggabungkan PjBL dengan teknologi dapat memperkuat kemampuan representasi matematis siswa dan memperkaya pembelajaran. Penelitian ini menyiratkan bahwa pembelajaran berbasis proyek yang didukung teknologi dapat menjadi model efektif untuk mendorong pendidikan matematika yang bermakna, menarik, dan berorientasi pada keterampilan di sekolah menengah.